Pemanfaatan Customer Internal Meaning Dalam Proses Komunikasi Pemasaran Pada Padmaning Garden - Bidhari, Kinanti Padma; Teguh, Monika (LPPM Stikosa - AWS, 2025)
As one of the largest ornamental plant-producing countries, Indonesia benefits from its fertile soil and tropical climate, making the cultivation of ornamental plants relatively easy. The agriculture industry in Indonesia, particularly the ornamental plant and nursery sector, has seen significant growth. One of the key players in this sector is Padmaning Garden, which has been operating since 2020 and handles both export and import sales. Over the course of four years, Padmaning Garden has successfully established and maintained its nursery business by implementing effective marketing communication strategies. This study examines the application of